Fundamental of Entrepreneurship ENT300 : Uni-Sport Center / Muhammad Nazrin Khairuddin ... [et al.] - Khairuddin, Muhammad Nazrin; Harun, Muhammad Amin; Johari, Johadzrin; Kamarudin, Mohamad Khairul Akma; Morhaili, Mohamad Taufik (2011)
In Kota Samarahan, have one company that also servicing futsal and badminton. So that we take want to take this opportunity to get involved in this type of business. Thus, there is only one competitor in Kota Samarahan which is Golden Hawk Company. Even though this business maybe have a competitor, we believe that we can success to fight against our competitor because we have a advantage that we providing a world class futsal and badminton service- In the future we believe that we can be the best company that providing futsal and badminton services in Kota Samarahan and perhaps whole Sarawak because we have a good management for customer, quality of service, worker, strategic place and pus provide a world standard sport. Besides, we also provide "take five café" a simple café which can refreshing our customer with isotonic drink.